Pengelolaan Program Jum’at Rohani (Jumroh) dalam Meningkatkan Karakter Religius pada Siswa di SDN 188 Bandung Baru - Amy Kurnia Rahmawati; Asep Dudi Suhardini; Arif Hakim (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research aims to determine the implementation of the spiritual Friday program in terms of philosophy, vision, mission, objectives, management, as well as supporting and inhibiting factors for the spiritual Friday program implemented at SDN 188 Bandung Baru. The method used in this research is a case study method with qualitative data. Researchers collected data using interview, observation and documentation techniques. The data sources in this research were Islamic religious education teachers, school principals, and students at SDN 188 Bandung Baru. The data analysis techniques used are data collection, reduction, data presentation, and drawing conclusions (verification). The results of this research generally show that (1) The philosophy of the spiritual Friday program is to create examples and familiarize students with Islamic religious teachings. The vision and mission are to instill noble morals in students. (2) Planning for spiritual Friday programs is carried out by Islamic religious education teachers and school principals. The organizational system is that each teacher and staff is given tasks and responsibilities in this program. The implementation consists of initial activities, core activities and final activities. The spiritual Friday program activities are continued with religious-based specialization classes which are the hallmark of this program, namely tahfidz, calligraphy, qiraat and qasidah classes. The supervision system is carried out by teachers and school principals. The evaluation system is carried out by holding evaluations every week. (3) Supporting factors for this program come from parents, teachers, staff, students, facilities and infrastructure. The inhibiting factors come from parents, weather, and other activities on Friday. Based on the research results, it can be concluded that the spiritual Friday program runs well and is effective in improving the religious character of students so that it can instill noble moral habits in students. Abstrak. Penelitian ini bertujuan untuk mengetahui pelaksanaan program jumat rohani yang ditinjau dari filosofi, visi, misi, tujuan, pengelolaan, serta faktor pendukung dan penghambat program jumat rohani yang dilaksanakan di SDN 188 Bandung Baru. Metode yang digunakan dalam penelitian ini adalah metode studi kasus dengan jenis data kualitatif. Peneliti mengumpulkan data menggunakan teknik wawancara, observasi, dan dokumentasi. Sumber data pada penelitian ini adalah guru pendidikan agama islam, kepala sekolah, dan siswa SDN 188 Bandung Baru. Adapun teknik analisis data yang digunakan yaitu pengumpulan data, reduksi, penyajian data, dan penarikan kesimpulan (verifikasi). Hasil penelitian ini secara umum menunjukkan bahwa (1) Filosofi program jumat rohani yaitu menciptakan keteladanan dan pembiasaan ajaran agama islam bagi siswa. Adapun visi dan misinya yaitu menanamkan akhlak mulia pada siswa. (2) Perencanaan program jumat rohani dilakukan oleh guru pendidikan agama islam dan kepala sekolah. Sistem pengorganisasiannya yaitu setiap guru dan staf diberikan tugas dan tanggungjawab dalam program ini. Pelaksanaan yang dilakukan terdiri dari kegiatan awal, kegiatan inti dan kegiatan akhir. Kegiatan program jumat rohani dilanjutkan dengan kelas peminatan berbasis keagamaan yang menjadi ciri khas dari program ini yaitu kelas tahfidz, kaligrafi, qiraat, dan qasidah. Sistem pengawasan dilakukan oleh guru-guru dan kepala sekolah. Adapun sistem evaluasi dilakukan dengan mengadakan evaluasi setiap minggunya. (3) Faktor pendukung adanya program ini berasal dari orangtua, guru, staf, siswa, sarana dan prasarana. Adapun faktor penghambatnya berasal dari orangtua, cuaca, dan adanya kegiatan lain di hari jumat. Berdasarkan hasil penelitian dapat disimpulkan bahwa program jumat rohani berjalan dengan baik dan efektif dalam meningkatkan karakter religius pada siswa sehingga dapat menanamkan pembiasaan akhlak mulia pada siswa.